Mechanism of Acid Reduction at Low and High Overpotential Metal Electrodes in the Presence and Absence of CO2: Implications for CO2 Reduction by N-Heterocycles - Zeitler, Elizabeth (Princeton, NJ : Princeton University, 2014)
Carbon dioxide reduction is of public interest to synthesize useful materials from CO2 and for storage of renewable energy in a carbon-constrained world. Scientifically, CO2 reduction is of fundamental interest to understand the activation of small molecules and stable chemical bonds. Pyridinium catalysts have been observed to lower the overpotential for reduction of CO2 to methanol at platinum and p-GaP electrodes. In this study, the reduction of pyridinium at a variety of metal electrode surfaces was explored along with its interaction with CO2. The reduction of any weak acid analyte on platinum was found to proceed via a one-electron, proton-coupled process forming H2. The reduction potential could be predicted entirely by acid pKa. Equilibrium and kinetic isotope effects supported this assignment. A prepeak feature observed for acid reductions was examined. Reduction forming a π-radical was observed for 4,4'-bipyridinium at platinum, gold and glassy carbon via spectroelectrochemistry. Only a small increase in radical decay was observed in the presence of CO2. Pyridinium reduction at gold was found to occur via proton reduction. Protonated and unprotonated N-heterocycle reductions on glassy carbon can best be explained via π-reduction. The interaction of CO2 with pyridine was examined. Current in the presence of CO2 was enhanced at slow scan rates due to the slow hydration of CO2 into carbonic acid, leading to pyridinium protonation and is not diagnostic of CO2 reduction. A variety of weak acid analytes showed current enhancement, with greater pKa values leading to greater enhancement. Solution buffering at the electrode interface by CO2 was examined. Current enhancement of pyridinium under CO2 was greater than the sum of the currents for background CO2 reduction and pyridinium reduction, indicating pyridine enhanced CO2 hydration.